Effects of a Group-Based Treadmill Program on Children With Neurodevelopmental Impairment Who Are Not Yet Ambulating. Issue 3 (2016) - Mattern-Baxter, Katrin
Abstract : Purpose: To examine the effects of a group-based treadmill program on gross motor skills related to walking and the amount of support needed for ambulation in children with neuromotor impairment who are not yet walking. Methods: Twelve children (mean age, 30.4 months; standard deviation, 7.9) participated in the program twice per week for 14 weeks. The Gross Motor Function Measure-88 Dimensions D and E (GMFM-88 D/E), the Functional Mobility Scale (FMS), the timed 10-m walk test, and the Pediatric Evaluation of Disability Inventory Mobility Scale (PEDI) were administered before and at the conclusion of the program. Data were analyzed using paired the t test and Wilcoxon matched-pairs signed rank test. Results: Statistically significant improvements were found between pre- and posttests in the GMFM-88 D ( P = .0005) and E ( P = .001), in FMS scores ( P = .039), and the PEDI ( P = .001). Conclusions: A group-based treadmill program leads to positive changes in walking ability in children with neuromotor impairment. Abstract : This is an examination of the effects of a group-based treadmill program on gross motor skills related to walking and the amount of support needed for children who are pre-ambulatory and with neuromotor impairment.